Parental Allowance in Serbia – Examining the World Health Organization Recommendations - Petar VASIĆ; Ivan MARINKOVIĆ (Transylvanian Review of Administrative Sciences, 2016)
This paper is one of the results of the project Research of Demographic Phenomena in the Function of Public Policies in Serbia, and is treating fertility as one of the major concerns of the current population development in Serbia. The aim of the paper is to analyze fertility levels in Serbia beyond the four basic recommendations proposed by the World Health Organization (WHO) regarding childbearing, and to give suggestions on how parental allowance could be reformulated if the recommendations were adopted. Birth levels and demographic structures are analyzed using demographic methods. Many European countries, including Serbia, are implementing the population policy trying to increase fertility levels to the replacement level. The legislative framework within which the pronatalist measures are being implemented was defi ned 13 years ago, and did not include all four WHO recommendations. The fi rst indications of the pronatalist measures failure have been visible during the past few years, consequently resulting in the need to evaluate their effects and redefi ne basic fi nancial measures. Having compared two basic fi nancial measures (parental leave and parental allowance), we believe that parental allowance is the key measure of the pronatalist policy, since it is realized on the basis of birth only (parental leave is realized on the basis of employment).